Half-Time Elementary School Counsellors: Teachers' Expectations of Role Versus Actual Activities - Madak, Paul R.; Gieni, Carol L. (Canadian Journal of Counselling and Psychotherapy, 2011)
Since poor role definition may create problems such as poor communication, service overlap/duplication, improper evaluation, diffuse goals and vague job descriptions, the present study investigated teacher expectations and actual role activities of five half-time elementary counsellors. Daily activity logs, kept for three weeks at three different times of the school year, and a survey completed by 141 teachers, were utilized in the data collection process. The findings were: (1) individual counselling and consulting with teachers accounted for the majority of counsellor time; (2) family problems other than divorce was the topic dealt with most frequently; (3) counsellors used their time differently in October than in May; (4) teachers disliked the half-time program; and (5) though inserviced, teachers were unclear on counsellor role.